Bioaccessibility of Trace Minerals from Different Oilseed Cakes Under In Vitro Conditions - Parihar, Deepti Singh; Mani, Veena; Kewalramani, Neelam; Gupta, Shiva; Kumar, Dhinesh; Kujur, S.T. Anjila (Indian Journal of Animal Nutrition, 2017)
The study was conducted to determine chemical composition, in vitro dry matter digestibility (IVDMD) and bioaccessibility of (%) of Iron (Fe), Manganese (Mn) and Cobalt (Co) in mustard (MC), cotton seed (CSC) and maize germ oil cake (MGOC). The values of DM, OM, CP, EE, NDF, ADF and TA in MC were 92.27, 92.43,38.36, 8.17, 28.11, 21.32 and 7.57%, respectively and the corresponding values in CSC were 92.16, 92.91, 21.11,6.26, 38.33, 31.14 and 7.09% and MGOC were 93.72, 96.42, 18.56, 8.86, 34.60, 23.71 and 3.58%. The MC, CSC and MGOC had Fe content of 275.54, 437.45 and 361.56 ppm, Mn content of 57.37, 28.10 and 27.34 ppm and Co level of 0.50, 0.45 and 0.30 ppm, respectively. IVDMD (%) was found to be the highest for MC (68.42±0.35) and the lowest for CSC (59.71±1.07). The ioaccessibility (%) of Fe from MC was 35.58±0.53 followed by MGOC (34.50±0.34) and CSC (30.38±0.47). Solubility or extent of release of Mn was higher (P<0.05) in MC (33.66±0.83%) followed by MGOC (32.17±0.26%) and CSC (26.82±0.58%). The bioaccessibity of Co was found higher in MGOC (33.21±0.27%) followed by MC (29.99±0.41%) and values were lower (P<0.05) for CSC (24.11±0.33%).